2019
DOI: 10.1371/journal.pone.0219083
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of frailty in a tertiary hospital: A point prevalence observational study

Abstract: Introduction Frailty is an important concept in modern healthcare due to its association with adverse outcomes. Its prevalence varies in the literature and there is a paucity of literature looking at the prevalence of frailty in an inpatient setting. Its significance lies on its impact on resource utilisation and costs. Aim To determine the prevalence of frailty in the adult population in a tertiary New Zealand hospital. Methods Eligible pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
6
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(78 citation statements)
references
References 32 publications
2
67
6
3
Order By: Relevance
“…As a result, this systematic review reports on studies with a mean age of > 75 years and no disease-specific diagnosis. Such studies are likely to include a high proportion of frail patients,24 but the number of frail patients in each study and their level of frailty is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, this systematic review reports on studies with a mean age of > 75 years and no disease-specific diagnosis. Such studies are likely to include a high proportion of frail patients,24 but the number of frail patients in each study and their level of frailty is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In view of this, the inclusion and exclusion criteria were developed to capture studies of mixed populations that would include a significant proportion of frail patients, as measured by a validated operationalisation of frailty, drawing on a previous systematic review in this area16 and reflecting other disease-specific reviews that have included mixed populations 23. A mean age criterion of 75 years was chosen in view of the strong correlation between frailty and older age (70% of hospitalised patients over the age of 75 years have been found to be frail),24 and this was combined with the absence of focus on a disease-specific terminal condition, for example, malignancy, organ failure or dementia. ACP was considered to be discussions with patients about their personal values, life goals and preferences regarding future medical care 21.…”
Section: Methodsmentioning
confidence: 99%
“…It can be the cause of incidents which worsen the frailty of older people [8]. The prevalence of frailty in geriatric inpatients, depending on the evaluation tool used, ranges from 48.8 to 80% [9,10]. Chen et al (2019) demonstrated that the prevalence of hospitalized frail older adults, evaluated with Fried's frailty phenotype, was 40% [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, these tools do not consider frailty—a clinical state of reduced physiologic reserve and increased vulnerability to poor health outcomes [ 12 ]—that is germane to clinical management of older adults. The prevalence of frailty ranges from 10 % in the community [ 13 ] to more than 50 % in the nursing homes [ 14 ] and hospitals [ 15 ], and it has been associated with poor health outcomes in the primary care [ 16 ], acute hospital [ 17 ], and critical care setting [ 18 ]. Therefore, assessing frailty on admission may provide information about patients’ vulnerability and prognosis that is not captured by the pneumonia severity and is useful to deliver patient-centered care to improve recovery.…”
Section: Introductionmentioning
confidence: 99%